GuideScan software for improved single and paired CRISPR guide RNA design - Perez, Alexendar R; Pritykin, Yuri; Vidigal, Joana A; Chhangawala, Sagar; Zamparo, Lee; Leslie, Christina S; Ventura, Andrea (Nature biotechnology, 2017)
A tool for genome-wide design of CRISPR guide RNAs reduces off-target effects and facilitates targeting of the non-coding genome. We present GuideScan software for the design of CRISPR guide RNA libraries that can be used to edit coding and noncoding genomic regions. GuideScan produces high-density sets of guide RNAs (gRNAs) for single- and paired-gRNA genome-wide screens. We also show that the trie data structure of GuideScan enables the design of gRNAs that are more specific than those designed by existing tools.